The practice of dentistry in intensive care units in Brazil - Blum, Davi Francisco Casa (Rev Bras Ter Intensiva, 2018)
OBJECTIVE: To evaluate the practice of dentistry in intensive care units. METHODS: An observational survey study was conducted in which questionnaires were sent via the online platform for collaboration in intensive care research in Brazil (AMIBnet). The study was carried out from June to October 2017. The questionnaires, which contained 26 closed questions about hospitals and dentistry practices in the intensive care units, were sent to 4,569 professionals from different specialties practicing in the units. RESULTS: In total, 203 questionnaires were returned, resulting in a response rate of 4.44%. Most of the responses were from intensive care units in the Southeast region of the country (46.8%). Public hospitals (37.9%) and private hospitals (36.4%) had similar participation rates. Of the respondents, 55% indicated that a bedside dentistry service was present, and they were provided in different ways. CONCLUSION: The presence of dentistry services and oral health service delivery training and protocols were correlated. The oral care methods varied greatly among the intensive care units surveyed.